Comprehensive study to investigate the role of various aminoglycoside resistance mechanisms in clinical isolates of Acinetobacter baumannii. Issue 2 (February 2017) - Sheikhalizadeh, Vajihe; Hasani, Alka; Ahangarzadeh Rezaee, Mohammad; Rahmati-yamchi, Mohammad; Hasani, Akbar; Ghotaslou, Reza; Goli, Hamid Reza
Abstract: Therapeutic resistance towards most of the current treatment regime by Acinetobacter baumannii has reduced the prescribing antibiotic pattern and option is being re-shifted towards more toxic agents including aminoglycosides. The present investigation aimed at to study various mechanisms towards aminoglycoside non-susceptibility in clinical isolates of A. baumannii . The bacteria were subjected to genetic basis assessment for the presence of aminoglycoside modifying enzymes (AME), 16S rRNA methylase encoding genes and relative expression of AdeABC and AbeM efflux pumps in relation to their susceptibility to five aminoglycosides. When isolates were subjected to typing by repetitive extragenic palindromic (REP) PCR, isolates could be separated into thirteen definite clones. The majority of isolates (94%) were positive for AME encoding genes. Possession of ant(2′)-Ia correlated with non-susceptibility towards gentamicin, amikacin, kanamycin, tobramycin; while, presence of aph(3′)-VIa attributed to resistance towards amikacin, kanamycin; possession of aac(3′)-Ia allied with non-susceptibility to amikacin, tobramycin and presence of aac(3′)IIa correlated with kanamycin non-susceptibility. Presence of armA was detected in 34.4%, 34.2%, 29.2%, 40.3%, and 64.2% of isolates showing non-susceptibility to gentamicin, amikacin, kanamycin, tobramycin and netilmicin, respectively. No isolates were found to carry rmtB or rmtC . Amikacin non-susceptibility in comparison to other aminoglycosides correlated with over production of adeB . Overall, the results represented a definitive correlation between presence of AME encoding genes as well as armA and resistance of A. baumannii towards aminoglycosides. On the other hand, the up-regulation of AdeABC and AbeM systems was found to have only the partial role in development of aminoglycoside resistance.